FAKTOR – FAKTOR YANG MEMPENGARUHI MUTU WEB TERHADAP KEPUASAN AKTIVITAS BELAJAR BAGI PENGGUNA WANITA - Merlina, Nita; Frieyadie, Frieyadie (Jurnal Pilar Nusa Mandiri, 2012)
This study aims to determine the factors that affect the quality of the web to satisfaction of learning activities for female users. Final model obtained in this study approached the research UTAUT (Unified Theory Of Aceptual and Use Of Technology) with data analysis using Structural Equation Modelling (SEM) on the software Analysis of Moment Structure (AMOS) version 6.0, a causal relationship between these factors which affect the quality of web-user satisfaction for women adalahVariabel beajar Performance Expectancy effect on Symbolic Adoption means the higher the student achievement expectations tehadap the greater web of learning opportunities to receive an online learning web mentally, Variable Effort Expectancy effect on Attitude Toward Technology means the higher expectations tehadap student effort, the greater web of learning attitude to receive online learning web, Social Influence Variables no effect on the Attitude Toward Technology college student means that studying the web with online learning medium was not influenced by others but their own consciousness to be able to learn the web, Variable Faciliting Condition effect on Symbolic Adoption means the student will receive an online learning web fasilatas when supported by adequate, Variable Attitude Toward Technology effect on Symbolic Adoption means the better the level of technology acceptance more likely to receive an online learning web mentally.